Plasmid Profiling and Antibiotic Resistance of Escherichia Coli and Escherichia Coli O157 Strains - Abd. Mutalib, Sahilah (1997)
Enterohaemorrhagic Escherichia coli O157:H7 has received considerable amount of attention because of its implication in sporadic outbreaks of hemorrhagic colitis, hemolytic uremic syndrome and thrombotic thrombocytopenic purpura. The incidence of E. coli O157:H7 have been reported in various parts of the world, however, its incidence in Malaysia is relatively unknown. From March to June 1996, 25 beef samples were obtained from 4 supermarkets in Selangcr and Federal Territory, Malaysia. Twenty five Po of beef samples were enriched in 225 ml of EC proth containing novobiocin (20 mg/l) for four hours at 37°C and were plated on MacConkey agar. Nineteen to fifty lactose fermenting colonies per sample (n=1091) were transferred onto Eosin Methylene Blue Agar, Sorbitol MacConkey Agar and Cefizime Tellurite Sorbitol MacConkey Agar. Sixty five of 112 metallic sheen and sorbitol negative colonies were Positive when tested for O157 antigen using latex agglutination test kit of Oxoid and Serobact. Nineteen (76%) samples were positive for E. coli O157:H7. The 65 strains of E. coli were tested for susceptibility against 20 antimicrobial agents and screened for plasmid DNA. All 65 isolates of O157 were resistant to four or more antimicrobial agent tested. All strains were resistant to bacitracin (100%), methicillin (100%) and vancomycin (100%). All strains were susceptible to cephalosporin, kanamycin, nalidixic acid and furazolidone. Fourty isolates contained plasmid ranging in sizes from 1.38 megadalton to 86.0 megadalton; and 29 possessed the 60.0 megadalton E. coli O157 serotype-specific plasmid (pOl57) of EHEC. Two of eight selected E. coli 0157 isolates were observed to transfer their resistant phenotypes at frequencies 2.7 X 1 0-7 to 3.0 X 1 0-6 per donor cells. The concomitant transfer of donor plasmids in two of the selected E. coli 0157 isolated was also detected. These results may suggest that antibiotic resistance among the selected E. coli 0157 isolates were encoded on conjugative R plasmids.